Ontario’s Electrical Future: Global Environmental Limits, Systems Thinking, and Electrical Power Planning in Ontario, 1974-1983 - Conway, Christopher (Scientia Canadensis, 2014)
In the mid-1970s, the Royal Commission on Electrical Power Planning (RCEPP) was ordered by the government of Ontario to review Ontario Hydro’s ambitious expansion plans. Historians have often considered the RCEPP an interesting but ineffective commission as changing economic factors, rather than the Commissions’ recommendations for slower growth, eventually slowed Hydro’s momentum in the early 1980s. This paper explores the Commission as an important venue for energy debate and as a means of facilitating research from public interest groups, including Energy Probe, in the late 1970s. From this debate the Commission negotiated ideas of “soft energy paths”, global resource limits, and cybernetic system thinking into a set of policy recommendations for democratic, systems-based electrical power planning. I argue that the tension between centralized control and local action found in the Commission’s systems approach to planning illustrates the difficulty of collective, long-term, and expert mediated, globalist planning in a period once thought of as a “dawning age of energy conservation.”